Method for preparing sodium-ion battery negative electrode material from bituminous coal
By using the method of nicotin coal -to -coal -preserved ion battery negative electrode materials, the problems of complex and high energy consumption of existing process were solved, and the preparation of high -performance negative materials was achieved. The first discharge ratio of capacity and cycle stability were significantly improved.
Patent Information
- Application Number
- CN202411512887.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
AI Technical Summary
The preparation process of existing sodium ion battery negative electrode materials has problems such as complex processes, low carbon yield, high energy consumption, and large acid consumption, which limits its kinetic performance in sodium ion battery systems.
Tobacco and coal are used as raw materials, and the negative materials of sodium ion battery are prepared through two main links: chemical heating and insulation. Specific steps include coal grinding, reaction with hybrid solution, dehydration, heating treatment, and high temperature carbonization, and finally disperse, remove magnetic and screen.
The prepared sodium-ion battery anode material has a first discharge specific capacity of 308.3mAh·g-1, a first efficiency of 88%, and a capacity retention rate of 91.6% after 100 cycles, which significantly improves the dynamic properties of the material.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery materials and relates to a method for preparing a sodium ion battery negative electrode material by utilizing bituminous coal. Background Art
[0002] Lithium-ion batteries, as a type of energy storage device with high energy density, have been widely used in large-scale energy storage systems such as electric vehicles and smart grids. However, their high manufacturing costs and the scarcity of lithium resources have made it difficult to meet the needs of future development. Finding low-cost secondary batteries with stable cycle performance as alternatives to lithium-ion batteries has gradually become a consensus solution.
[0003] Compared to lithium, sodium has similar chemical properties and is abundant and inexpensive. Therefore, sodium-ion batteries (SIBs) offer a promising alternative to lithium-ion batteries for large-scale energy storage. Consequently, the development of high-performance SIB anode materials is a hot topic. In recent years, carbon has emerged as one of the most promising anode materials due to its excellent electronic conductivity, tunable microstructure, low preparation cost, and low potential. However, because the radius of sodium ions is larger than the interlayer spacing of graphite, graphite anode materials cannot be used in SIBs. Various strategies have been proposed to prepare non-graphitizable carbon materials for SIBs, but most methods suffer from complex processes, low carbon yields, high energy consumption, and high acid consumption, significantly reducing the cost advantages of these materials. Furthermore, the low electronic conductivity and difficult-to-control pore structure of SIBs significantly limit their kinetic performance in SIBs. Therefore, developing low-cost preparation methods for high-performance SIBs is crucial for promoting the commercialization of SIBs. Summary of the Invention
[0004] The present invention overcomes the shortcomings of the prior art and proposes a method for preparing a negative electrode material for sodium ion batteries using bituminous coal. The present invention is achieved through the following technical solutions: A method for preparing a negative electrode material for a sodium ion battery using bituminous coal comprises the following steps: S1. Grind bituminous coal to a pulverized coal with a D50 of 18±2 μm; the bituminous coal has an ash content of ≤8% and a moisture content of ≤10%; S2, adding pulverized coal and mixed acid solution into a reactor and stirring for 15-20 hours, then deacidifying, washing and drying; S3. The dried pulverized coal is heated in two stages: in the first stage, the temperature is raised from room temperature to 180-220°C at a rate of 4-6°C / min and maintained at this temperature for 1.5-3 hours; in the second stage, the temperature is further raised to 280-320°C at a rate of 8-12°C / min and maintained at this temperature for 1.5-3 hours. After cooling, the pulverized coal is rinsed to a pH of 6-6.5 and then dried; S4, carbonizing the material obtained in step S3 using a high-temperature carbonization furnace, directly raising the temperature from room temperature to 1300-1400°C at a heating rate of 4-6°C / min, then maintaining the temperature at 1300-1400°C for 5.5-6.5 hours, and then cooling to room temperature; S5. The material obtained in step S4 is sequentially subjected to breaking up, demagnetization and screening processes.
[0005] Preferably, the bituminous coal in step S1 is sequentially subjected to flotation, drying and crushing by a crusher.
[0006] More preferably, the particle size of the bituminous coal after crushing is ≤1mm.
[0007] Preferably, the mixed acid solution comprises boric acid and hydrofluoric acid, the boric acid concentration is 3-5%, and the HF concentration is 12-14%; the weight ratio of the mixed acid solution to the coal powder is 2.5-3.5:1.
[0008] Preferably, the deacidification in step S2 is performed by filter pressing, and then the filter cake is washed until the pH is greater than 3.
[0009] More preferably, the cleaning and drying in step S2 is to put the cleaned filter cake into a rinsing bucket, add sodium citrate, stir and clean, then filter press and then vacuum dry.
[0010] More preferably, the stirring time of adding sodium citrate is greater than 4 hours.
[0011] Preferably, the breaking up is performed using a breaking machine to break up the particles to a D50 of 16±2 μm.
[0012] Preferably, the screening is performed using an ultrasonic vibration screen with a screen size of 320 mesh.
[0013] Preferably, the carbonization temperature is 1350° C., under nitrogen protective atmosphere, the carbonization time is 2 hours, and then cooled to room temperature.
[0014] The beneficial effects of the present invention compared to the prior art are: The present invention uses bituminous coal as raw material and successfully prepares sodium ion battery negative electrode materials through two main steps: chemical heating, heat preservation, ash removal, and carbonization. The sodium ion battery negative electrode material prepared by the present invention can achieve an initial discharge specific capacity of 308.3 mAh g -1 The initial efficiency is 88%, and after 100 cycles, its capacity retention rate reaches 91.6%. DETAILED DESCRIPTION
[0015] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail with reference to the embodiments. It should be understood that the specific embodiments described herein are merely for explaining the present invention and are not intended to limit the present invention. The technical solutions of the present invention will be described in detail below with reference to the embodiments, but the scope of protection is not limited thereto.
[0016] Example 1 This embodiment provides a method for preparing a negative electrode material for a sodium ion battery using bituminous coal, and the specific steps are as follows: S1. Select the bituminous coal (ash content 8%) after flotation, dry it to 10% moisture, and then crush it to a particle size of ≤1mm using a hammer crusher.
[0017] S2. The pulverized coal powder obtained in step S1 is crushed by a Raymond mill until D50 is 18±2 μm.
[0018] S3. Select a plastic reactor and prepare 180 kg of a mixed acid solution of boric acid and hydrofluoric acid in advance. The boric acid concentration in the mixed acid solution is required to be 4% and the HF concentration is required to be 13%.
[0019] S4: 60 kg of the coal powder obtained in step S2 was added to a plastic reactor, stirred, and reacted for 16 hours. The mixture was then filtered to remove the acid, and the filter cake was washed until the pH was greater than 3. 0.5 kg of sodium citrate was then added to a rinse bucket, stirred for 4 hours, and then filtered again. The mixture was then vacuum dried.
[0020] S5. The pulverized coal obtained in step S4 is heated in a rotary kiln in two stages: the first stage is heating from room temperature to 200°C at a rate of 5°C / min, held at that temperature for 2 hours; the second stage is heating from 200°C to 300°C at a rate of 10°C / min, held at that temperature for 2 hours, and then cooled to room temperature. The pulverized coal is then rinsed to a pH of 6 and then dried.
[0021] S6. Carbonize the material obtained in step S5 using a high-temperature carbonization furnace, directly heating the temperature from room temperature to 1350° C. at a heating rate of 5° C. / min, maintaining the temperature at 1350° C. for 6 hours, and then cooling to room temperature.
[0022] S7. The material obtained in step S6 is broken up using a breaker until D50 is 16±2 μm.
[0023] S8. Demagnetize the material obtained in step S7 using a demagnetizer.
[0024] S9. The material obtained in step S8 is sieved using an ultrasonic vibration sieve with a sieve size of 320 mesh.
[0025] The first discharge capacity of the sodium ion battery negative electrode material prepared in Example 1 was measured to be 308.3 mAh·g -1The initial efficiency is 88%, and after 100 cycles, its capacity retention rate is 91.6%.
[0026] Example 2 This embodiment provides a method for preparing a negative electrode material for a sodium ion battery using bituminous coal, and the specific steps are as follows: S1. Select the bituminous coal (ash content 6%) after flotation, dry it to 8% moisture, and then use a hammer crusher to crush it to a particle size of ≤1mm.
[0027] S2. The pulverized coal powder obtained in step S1 is crushed by a Raymond mill until D50 is 18±2 μm.
[0028] S3. Select a plastic reactor and prepare 180 kg of a mixed acid solution of boric acid and hydrofluoric acid in advance. The boric acid concentration in the mixed acid solution is required to be 4% and the HF concentration is required to be 13%.
[0029] S4: 60 kg of the coal powder obtained in step S2 was added to a plastic reactor, stirred, and reacted for 16 hours. The mixture was then filtered to remove the acid, and the filter cake was washed until the pH was greater than 3. 0.5 kg of sodium citrate was then added to a rinse bucket, stirred for 6 hours, and then filtered again. The mixture was then vacuum dried.
[0030] S5. The pulverized coal obtained in step S4 is heated in a rotary kiln in two stages: the first stage is heating from room temperature to 180°C at a rate of 4°C / min, held at that temperature for 3 hours; the second stage is heating from 180°C to 280°C at a rate of 8°C / min, held at that temperature for 1.5 hours, and then cooled to room temperature. The pulverized coal is then rinsed to a pH of 6 and then dried.
[0031] S6. Carbonize the material obtained in step S5 using a high-temperature carbonization furnace, directly raising the temperature from room temperature to 1400° C. at a heating rate of 6° C. / min, maintaining the temperature at 1400° C. for 6.5 hours, and then cooling to room temperature.
[0032] S7. The material obtained in step S6 is broken up using a breaker until D50 is 16±2 μm.
[0033] S8. Demagnetize the material obtained in step S7 using a demagnetizer.
[0034] S9. The material obtained in step S8 is sieved using an ultrasonic vibration sieve with a sieve size of 320 mesh.
[0035] The first discharge capacity of the sodium ion battery negative electrode material prepared in Example 2 was measured to be 300.6 mAh·g -1 The initial efficiency is 86.5%, and after 100 cycles, its capacity retention rate is 89.2%.
[0036] Example 3 This embodiment provides a method for preparing a negative electrode material for a sodium ion battery using bituminous coal, and the specific steps are as follows: S1. Select the bituminous coal (ash content 5%) after flotation, dry it to 10% moisture, and then crush it to a particle size of ≤1mm using a hammer crusher.
[0037] S2. The pulverized coal powder obtained in step S1 is crushed by a Raymond mill until D50 is 18±2 μm.
[0038] S3. Select a plastic reactor and prepare 180 kg of a mixed acid solution of boric acid and hydrofluoric acid in advance. The boric acid concentration in the mixed acid solution is required to be 4% and the HF concentration is required to be 13%.
[0039] S4: 60 kg of the coal powder obtained in step S2 was added to a plastic reactor, stirred, and reacted for 16 hours. The mixture was then filtered to remove the acid, and the filter cake was washed until the pH was greater than 3. 0.5 kg of sodium citrate was then added to a rinse bucket, stirred for 5 hours, and then filtered again. The mixture was then vacuum dried.
[0040] S5. The pulverized coal obtained in step S4 is heated in a rotary kiln in two stages: the first stage is heating from room temperature to 220°C at a rate of 6°C / min, held at that temperature for 1.5 hours; the second stage is heating from 220°C to 320°C at a rate of 12°C / min, held at that temperature for 3 hours, and then cooled to room temperature. The pulverized coal is then rinsed to a pH of 6.5 and then dried.
[0041] S6. Carbonize the material obtained in step S5 using a high-temperature carbonization furnace, directly raising the temperature from room temperature to 1300° C. at a heating rate of 4° C. / min, maintaining the temperature at 1300° C. for 5.5 hours, and then cooling to room temperature.
[0042] S7. The material obtained in step S6 is broken up using a breaker until D50 is 16±2 μm.
[0043] S8. Demagnetize the material obtained in step S7 using a demagnetizer.
[0044] S9. The material obtained in step S8 is sieved using an ultrasonic vibration sieve with a sieve size of 320 mesh.
[0045] The first discharge capacity of the sodium ion battery negative electrode material prepared in Example 3 was measured to be 295.6 mAh·g -1 The initial efficiency is 84%, and after 100 cycles, its capacity retention rate is 88.2%.
[0046] Example 4 This embodiment provides a method for preparing a negative electrode material for a sodium ion battery using bituminous coal, and the specific steps are as follows: S1. Select the bituminous coal (ash content 8%) after flotation, dry it to 9% moisture, and then crush it to a particle size of ≤1mm using a hammer crusher.
[0047] S2. The pulverized coal powder obtained in step S1 is crushed by a Raymond mill until D50 is 18±2 μm.
[0048] S3. Select a plastic reactor and prepare 180 kg of a mixed acid solution of boric acid and hydrofluoric acid in advance. The boric acid concentration in the mixed acid solution is required to be 5% and the HF concentration is required to be 12%.
[0049] S4: 60 kg of the coal powder obtained in step S2 was added to a plastic reactor, stirred, and reacted for 16 hours. The mixture was then filtered to remove the acid, and the filter cake was washed until the pH was greater than 3. 0.5 kg of sodium citrate was added to a rinse bucket, and the mixture was stirred for 5.5 hours before being filtered again. The mixture was then vacuum dried.
[0050] S5. The pulverized coal obtained in step S4 is heated in a rotary kiln in two stages: the first stage is heating from room temperature to 200°C at a rate of 6°C / min, held at this temperature for 2 hours; the second stage is heating from 200°C to 320°C at a rate of 12°C / min, held at this temperature for 2 hours, and then cooled to room temperature. The pulverized coal is then rinsed to a pH of 6.5 and then dried.
[0051] S6. Carbonize the material obtained in step S5 using a high-temperature carbonization furnace, directly heating the temperature from room temperature to 1350° C. at a heating rate of 4° C. / min, maintaining the temperature at 1350° C. for 5.5 hours, and then cooling to room temperature.
[0052] S7. The material obtained in step S6 is broken up using a breaker until D50 is 16±2 μm.
[0053] S8. Demagnetize the material obtained in step S7 using a demagnetizer.
[0054] S9. The material obtained in step S8 is sieved using an ultrasonic vibration sieve with a sieve size of 320 mesh.
[0055] The first discharge capacity of the sodium ion battery negative electrode material prepared in Example 4 was measured to be 305.1 mAh·g -1 The initial efficiency is 87%, and after 100 cycles, its capacity retention rate is 91.1%.
[0056] Comparative Example 1 Comparative Example 1 provides a method for preparing a negative electrode material for a sodium ion battery using bituminous coal, wherein: S5. The pulverized coal obtained in step S4 is heated in a rotary kiln: the temperature is raised from room temperature to 300°C at a rate of 10°C / min, maintained at this temperature for 4 hours, and then cooled to room temperature. The pulverized coal is then rinsed to a pH of 6 and then dried.
[0057] S6. Carbonize the material obtained in step S5 using a high-temperature carbonization furnace, directly heating the temperature from room temperature to 1550° C. at a heating rate of 5° C. / min, maintaining the temperature at 1550° C. for 6 hours, and then cooling to room temperature.
[0058] The remaining steps are the same as those in Example 1.
[0059] The first discharge capacity of the sodium ion battery negative electrode material prepared in Comparative Example 1 was 269.4 mAh g -1 The initial efficiency is 73%, and after 100 cycles, its capacity retention rate is 80.6%.
[0060] Comparative Example 2 Comparative Example 2 provides a method for preparing a negative electrode material for a sodium ion battery using bituminous coal, wherein step S5 is omitted and carbonization is performed directly, and the remaining steps are the same as those in Example 1.
[0061] The first discharge capacity of the sodium ion battery negative electrode material prepared in Comparative Example 2 was 220.8 mAh g -1 The initial efficiency is 65%, and after 100 cycles, its capacity retention rate is 72.6%.
[0062] The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be considered that the specific embodiments of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, they can make several simple deductions or substitutions without departing from the present invention, which should be regarded as belonging to the scope of patent protection determined by the submitted claims of the present invention.
Claims
1. A method for preparing a negative electrode material for a sodium ion battery using bituminous coal, characterized in that: The following steps are involved: S1. Grind the bituminous coal to a coal powder with a D50 of 18±2 μm; the bituminous coal has an ash content of ≤8% and a moisture content of ≤10%; S2, adding coal powder and mixed acid solution into a reactor and stirring for 15-20 hours, then deacidifying, washing and drying; S3, the dried pulverized coal is heated in two stages: the first stage is heated from room temperature to 180-220°C at a rate of 4-6°C / min, and kept at a constant temperature for 1.5-3h; the second stage is continued to be heated to 280-320°C at a rate of 8-12°C / min, and kept at a constant temperature for 1.5-3h, and then rinsed to a pH of 6-6.5 after cooling, and then dried; S4, carbonizing the substance obtained in step S3 using a high-temperature carbonization furnace, directly raising the temperature from room temperature to 1300-1400°C, with a heating rate of 4-6°C / min, then maintaining the temperature at 1300-1400°C for 5.5-6.5h, and then cooling to room temperature; S5. The material obtained in step S4 is sequentially subjected to breaking, demagnetization and screening processes.
2. The method for preparing a negative electrode material for a sodium ion battery using bituminous coal according to claim 1, characterized in that: The bituminous coal described in step S1 is sequentially subjected to flotation, drying and crushing by a crusher.
3. The method for preparing a negative electrode material for a sodium ion battery using bituminous coal according to claim 2, characterized in that: The particle size of the bituminous coal after crushing is ≤1mm.
4. The method for preparing a negative electrode material for a sodium ion battery using bituminous coal according to claim 1, characterized in that: The mixed acid solution includes boric acid and hydrofluoric acid, the boric acid concentration is 3-5%, and the HF concentration is 12-14%; the weight ratio of the mixed acid solution to the coal powder is 2.5-3.5:
1.
5. The method for preparing a negative electrode material for a sodium ion battery using bituminous coal according to claim 1, characterized in that: The deacidification in step S2 is performed by filter pressing, and then the filter cake is washed until the pH value is greater than 3.
6. The method for preparing a negative electrode material for a sodium ion battery using bituminous coal according to claim 5, characterized in that: The cleaning and drying described in step S2 is to put the cleaned filter cake into a rinsing bucket, add sodium citrate, stir and clean, then filter press, and then vacuum dry.
7. The method for preparing a negative electrode material for a sodium ion battery using bituminous coal according to claim 6, characterized in that: The stirring time after adding sodium citrate is greater than 4 hours.
8. The method for preparing a negative electrode material for a sodium ion battery using bituminous coal according to claim 1, characterized in that: The dispersion is performed by using a dispersion machine to disperse the particles until D50 is 16±2 μm.
9. The method for preparing a negative electrode material for a sodium ion battery using bituminous coal according to claim 1, characterized in that: The sieving is performed using an ultrasonic vibration sieve with a sieve size of 320 meshes.
10. The method for preparing a negative electrode material for a sodium ion battery using bituminous coal according to claim 1, characterized in that: The carbonization temperature is 1350° C., under a nitrogen protective atmosphere, the carbonization time is 2 hours, and then cooled to room temperature.